MULTICHANNEL SATELLITE QUANTUM KEY DISTRIBUTION SYSTEMS USING SCM-WDM - Hiền (Journal of Military Science and Technology, 2021)
Quantum key distribution (QKD is a solution capable of achieving unconditional security by applying the law of quantum mechanics to distribute a secure key between two legitimate parties in the presence of an eavesdropper. Using satellites to distribute quantum keys to ground stations over a free space optical (FSO) channel is a promising solution in creating a global QKD network. However, due to the influence of the FSO channel, especially atmospheric disturbances, the secret key rate (SKR) of current QKD systems is limited. Therefore, this study proposes a model of multichannel QKD system based on wavelength division multiplexing (WDM) and subcarrier multiplexing (SCM) to increase the SKR. Based on theoretical analysis with the tools of mathematics and probability, the authors have developed formulas to calculate SKR and quantum bit error rate of the proposed system. Numerical results show that multichannel QKD systems allow for improved SKR compared to single-channel systems while still meeting QBER requirements.